Let $M$ be a $2 \times 2$ matrix with coefficients in $\mathbb{Z}_{\ell}$ whose characteristical polynomial is

$$ P(T) = T^2- (a+d) T + (ad-bc). $$

I've encountered the following assertion: If $P(T)$ factors over $\mathbb{Z}/\ell \mathbb{Z}$ as

$$ P(T) = (T-\lambda_1)(T-\lambda_2) $$ with $\lambda_1 \not\equiv \lambda_2 \pmod{\ell}$, then in fact $M$ is diagonalizable over $\mathbb{Z}_{\ell}$.

I was able to prove this using a straightforward argument by diagonalizing over $\mathbb{Z}/\ell \mathbb{Z}$ and then explicitly lifting. However, I was wondering if there was a more conceptual way to explain this in terms of Hensel's Lemma or something (i.e. a more conceptual way to package this lifting argument).


Let $R$ be a local henselian ring (e.g. complete local rings) with residue field $k$. Let $\phi$ be an endomorphism of $V=R^n$ such that its characteristic polynomial $P(T)\in R[T]$ is completely split and separable in $k[T]$. Then $\phi$ is diagonalizable over $R$.

First by Hensel property, $P(T)$ is completely split and separable in $R[T]$ (this is the only place we use henselian hypothesis). Denote by $a_1, \dots, a_n\in R$ the eigenvalues of $\phi$ and by $V_{a_i}$ the eigensubspace $\mathrm{ker}(\phi - a_i I_n)\subseteq V$. The point is to prove that $V=\oplus_{1\le i\le n} V_{a_i}$. As the submodules $V_{a_i}$ are in direct sum (note that $a_i-a_j$ is an unit in $R$ if $i\ne j$), it is enough to show that $V=\sum_{1\le i\le n} V_{a_i}$.

Consider the sub-$R$-algebra $A=R[\phi]$ of $\mathrm{End}(V)$ generated by $\phi$. For any $i\le n$, let $$ e_i=\prod_{j\ne i} (\phi-a_j I_n)\in A.$$ We have $\phi e_i=(\phi-a_i I_n)e_i + a_i e_i=P(\phi)+a_ie_i=a_ie_i$. So $e_iV\subseteq V_{a_i}$ and it is enough to show that $I_n\in \sum_i e_iA$ or, equivalently, that $e_1, \dots, e_n$ generate the unit ideal of $A$. But all these properties are true over the residue field $k$ of $R$ by the diagonalizability condition over $k$. So $$A\otimes_R k=\sum_{1\le i\le n} \bar{e}_i A\otimes_R k.$$ (Of course this can also be checked directly over $k$.) Thus $$ A/(\sum_i e_iA) \otimes_R k=0$$ and $A=\sum_i e_iA$ by Nakayama's lemma.

  • $\begingroup$ Thanks! Exactly the kind of thing that I was looking for. $\endgroup$ – Tony Jan 6 '13 at 15:09

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.